Diagnóstico sectorial del grupo empresarial construcción de los cantones Paltas, Catamayo, Gonzanamá y Cariamanga. - Cuenca Rojas, Karen Giomar (2024)
The sectoral diagnosis includes a detailed evaluation of a specific sector of the economy, with the purpose of knowing its current situation, therefore, it is of great importance to detect the areas that require attention, as well as the opportunities that can be taken advantage of to improve the performance of the sector. The objective that guided the research work is to carry out a sectorial diagnosis of the construction business group in the cantons of Paltas, Catamayo, Gonzanamá and Cariamanga. A methodology with a quantitative approach was used, using the deductive method, the research was characterized as exploratory and descriptive type and scope, the design was non- experimental transversal, the research technique was the survey applied to the respective managers of the companies. The sector has 33 companies in the 4 cantons of the construction activity of section F of the International Standard Industrial Classification (ISIC). The main results allowed the identification of key success factors, financial and non-financial performance indicators. Finally, it was concluded that the sector's return on total assets (ROA) is 0.13, which indicates a modest profitability in relation to total assets; equity indebtedness is 0.89; asset indebtedness averages 0.47; net profit margin is 0.13; net profit margin is 0.13; net profit margin is 0.47; net profit margin is 0.13; net profit margin is 0.47; net profit margin is 0.13; and net profit margin is 0.47; net profit margin 0.13, which indicates that the companies are efficient in controlling their costs and generating profits, and sales turnover with an average of 1.64. As non-financial indicators, the average advertising investment is 0.01 and personnel training is 0.06, which indicates a low level of investment in personnel training.